Using Carbon Revenues - World Bank (World Bank, Washington, DC, 2019)
Carbon pricing is increasingly recognized as an important source of government revenue. Carbon revenues can be crucial in supporting cost-effective climate mitigation, industrial competitiveness and other economic and development objectives. How carbon revenues are used and how these uses are communicated are also critical for public and stakeholder acceptability of carbon pricing. This report provides practical guidance on using carbon revenues by helping policymakers understand the implications, opportunities, and challenges associated with different approaches to carbon revenue use.